Encapsulação da rifampicina em matrizes poliméricas flutuantes obtidas por liofilização a partir de metilcelulose e ftalato de hidroxipropilmetilcelulose. Avaliação da liberação in vitro - Zaniboni, Heny Cássia [UNESP]; Peres Peres, Pollyana Gisele [UNESP]; Scarpa, Maria Virgínia [UNESP]; Oliveira, Anselmo Gomes de [UNESP] (My University, 2001)
Floating multiparticles for oral administration with different compositions were studied from a matricial polymeric system to obtain sustained release. The polymers used in the multiparticles constitution were methylceullose (MC) and hydroxypropylmethylcelullose phthalate (HPMCP) in several proportions. Spherical and isolated structures were obtained using HPMCP/MC in the range from 1:3 to 1: 13. The diameters of the floating multiparticles were in the range from 3 to 3.25 mm, while the non-floating particles were between 1.75 and 2.1 mm. The morphological analysis by confocal microscopy showed that the probable mechanism of drug release was the diffusion from the inner of particles to external media. The encapsulation of hydrophilic model substances (tartrazin and bordeaux S), showed that the maximum incorporation was about 38%, while for the lipophilic model substances (rifampicin) was 45%. The in vitro release of rifampicin in acid medium was dependent on the ratio HPMCP/MC. In alkaline medium the release followed a two-step profile, with slow release in the initial times and subsequent increase in the higher times The initial drug delivery profile was not dependent on the MC/HPMCP ratio and can be related with the release of the antibiotic from multiparticle inner caused by the swelling of polymers by the presence of water in the system. However, afterwards the release proceeds with typical profile of process involving hydrogels systems.
Rifampicin encapsulation in floating polymeric matrix obtained from methyl cellulose and hydroxipropylmethylcellulose and in vitro drug release analysis
Keywords: Floating multiparticles; In vitro drug release; Polymeric matrix; Rifampicin; a15lv; amaranth; hydroxypropylmethylcellulose; methylcellulose; rifampicin; tartrazine; acidity; alkalinity; confocal microscopy; drug delivery system; drug diffusion; drug formulation; drug solubility; drug structure; hydrogel; hydrophilicity; in vitro study; lipophilicity; particle size; polymerization; structure analysis; sustained drug release